(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2025)
The capture fishery of squid (Loligo chinensis) in the Bangka Belitung Islands Province, particularly at TPI Batu Belubang, is an important sector in supporting food security and the local economy. Squid, being a high-economic value commodity, is greatly influenced by environmental factors and seasonal patterns, thus requiring a sustainable management approach. This study aims to analyze the seasonal catch patterns of squid using the Seasonal Catch Index (IMP) method based on Catch Per Unit Effort (CPUE) data over the period of 2020–2024. The analysis results indicate significant seasonal fluctuations, with the highest IMP value in November (230.78%) and the lowest in March (23.16%), generally correlating with oceanographic conditions such as water temperature and nutrient availability, which influence squid distribution. These findings underscore the necessity of season-based fishery management strategies, including quota regulation, temporary closures during low seasons, and regular utilization of CPUE data, to sustain squid stocks and enhance catch efficiency in the future. Key words: CPUE, squid, seasonal index, fisheries management, TPI Batu Belubang